Juridical Analysis of the Amount of Diyat Toward Armed Conflict Victims in Aceh - Munawarsyah Munawarsyah; Januddin Januddin; Muhammad Jafar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Islamic criminal law recognizes a kind of punishment called as diyat (compensation) for victims of murder and torture which has been apologized by the victim or family of victim. Diyat is amount of money or properties that should be paid by the perpetrator due to the death or damage of victim body. The legal basis for the determination of diyat can be found in Koran, chapter Al-Baqarah verse 178. Apart from that, there is Hadist of Muhammad Prophet written by Abu Dawud (peace be upon him), explaining the amount of diyat based on crime category whether murder or torture.Aceh Governance has implemented this kind of punishment as a solution on criminal offences in realizing and fulfilling justice for armed conflict victims since 2002. In providing the policy of such payment for the victims in Aceh is based on the assumption that they are under the responsibility of state, therefore the government has determined the compensation on them. The amount of the compensation provided for the victims is not equal to the amount ruled by Islamic criminal law. Therefore, it is interesting to explore regarding the concept becoming the basic for determining it by Aceh Government, and compared it to the amount ruled by the law.The research reveals that the sum of money for the compensation of what called diyat based on Islamic criminal law is the standard concept but it can be replaced by sum of money or properties that have equal price. The basic rules for this punishment in Islamic criminal law can be found in Al-Baqarah verse 178 of Koran. Moreover, regarding the sum of payment that should be provided can be found in Hadith of Prophet of Muhammad Peace be upon him which is told by Imam Abu Daud, mercy Allah for him. Practically, in Islamic criminal law the court, responsible persons and a due date for the payment must decide it.  The rule consisting in the Islamic law is really different from the implementation of compensation done by Aceh Government towards the victims in Aceh. It is recommended that the Aceh Government should realize the rules of the sum of compensation that should be received by the victims or the families based on the determination of the Court as a legal basis. In addition, the Central government as the main responsible party in repairing the condition of the society after the conflict should become the priority and absolute. The law enforcement in fulfilling the rights in Aceh should be done by involving some parties especially priest. Hence the society of the victims in Aceh obtains justice and legal certainty to get their rights.